Spontaneous gastric perforation in an 11-year-old boy with anorexia nervosa: rare presentation with right iliac fossa pain. (7th September 2012) - Hashmi, Khawar Sibtain; Ellul, Thomas; Leopard, Daniel Charles; Woodward, Alan
Abstract : Spontaneous gastric perforation is rare in children. It is usually associated with prematurity, foreign bodies and trauma. Anorexia nervosa (AN) can be an underlying condition although no cases are reported in the literature. We are reporting a rare case of 1- year-old boy with AN who presented with right iliac fossa (RIF) pain mimicking acute appendicitis. Intraoperative findings proved a gastric perforation. Pathophysiology of this condition in AN is poorly understood. Gastric smooth muscle atrophy and ischaemia can be the possible underlying mechanisms. The case discussed here highlights the fact that any abdominal pain in patients with underlying eating disorders (EDs) should raise suspicion of perforation as diagnosis can be far more complicated.